Measures to counteract the negative effects of night work - Ståle Pallesen; Bjørn Bjorvatn; Nils Magerøy; Ingvild Berg Saksvik; Siri Waage; Bente Elisabeth Moen (Nordic Association of Occupational Safety and Health (NOROSH), 2010)
OBJECTIVES: Night work is associated with several negative health outcomes as well as accidents and reduced productivity. The aim of this study was to identify factors that may counteract the negative effects of night work. METHODS: We conducted searches for studies of scientifically based countermeasures of the negative effects of night work in PubMed and Thomson Reuters' ISI Web of Knowledge© and inspected the reference lists of relevant literature. RESULTS: We identified studies describing countermeasures such as proper personnel selection, bright light therapy, melatonin administration, naps, exercise, sleepiness detection devices, and the use of stimulants to improve wakefulness and hypnotics to improve daytime sleep. CONCLUSIONS: There is some research supporting countermeasures (eg, bright light, melatonin, naps, use of stimulants, proper work scheduling) as a means to improve adaptation to night work. However, there is little evidence that such countermeasures reduce the long-term health consequences of night work. Future studies should aim at identifying both work and individual factors which are related to differential health outcomes of night work. Better study designs (eg, longitudinal designs and use of standardized outcome measures) are needed in future research.